Formulation of Small Quantity Lipid-based Nutrient Supplement (SQ-LNS) Tablet from Soybean: A Preventive Approach on Stunted Birth for Pregnant and Breastfeeding Women - Virginia Heaven Mariboto Siagian; Johnessa Cung; Spica Diani Anandawijaya; Sandya Amelia Febriliani; Avika Widyapuspita; Iyan Sopyan (Universitas Sebelas Maret, 2025)
The prevalence of stunting in Indonesia, which has not met the requirements of the WHO, makes stunting a national problem. In line with the nutritional intervention in 2020-2030, UNICEF developed SQ-LNS products as a food paste. As an effort to prevent stunting as well as improve product stability, the formulation of Small-Quantity Lipid-based Nutrient Supplements (SQ-LNS) from soybeans (Glycine max (L.) Merr) in tablet form is proposed to be a solution for pregnant and breastfeeding women. Microencapsulation technology is used to entrap soybean oil as the lipid source of this supplement. This study aims to obtain the best concentration of maltodextrin, soy protein isolate, and carboxymethyl cellulose as a soybean oil coating for felting into SQ-LNS tablet preparation. The best microcapsule is produced from a 40% formula with a percent yield of 28%, encapsulation efficiency of 79.83%, PSD microcapsule of 1.003 μm, and round agglomerated particles with a smooth surface without any residual oil seen under the SEM, and obtained the best formulation and evaluation of SQ-LNS tablets so that they meet the quality standards of good stunting supplement tablets.